A literature review on negative effects of coaching – what we know and what we need to know. Issue 1 (2nd January 2019) - Schermuly, Carsten C.; Graßmann, Carolin
ABSTRACT: Coaching can have tremendous positive effects, but to date, there has been little attention to the possibility that coaching can also exhibit negative effects. To fill this void, this literature review introduces the concepts of negative effects of coaching for clients, coaches and organisations to a wide audience of coaching researchers and practitioners. In a synthesis of the literature, it illuminates which negative effects can emerge, how frequently and intensely they occur, and which antecedents can explain their occurrence. Nine different studies with a qualitative, cross-sectional, time-lagged, or experimental research orientation were identified and used for this review. Throughout the diverse studies, negative effects occurred frequently, but only a few of them were severe and most of them were low in intensity. Concerning their antecedents, higher relationship quality between clients and coaches was related to fewer negative effects. The findings also indicated a beneficial influence of supervision. Moreover, negative effects for clients and negative effects for coaches were interrelated. These findings contribute to the professionalisation of coaching and put coaching in line with other helping relationships, where negative effects have been acknowledged as natural occurrences without being taboo.